Traumatic testicular dislocation - Yi-Chen Chiu, MD; Yen-Ko Lin, MD, PhD; Maya Saranathan. (Medicine, 2022)
Abstract. Introduction:. Traumatic testicular dislocation is an uncommon complication of blunt scrotal injury and is easily overlooked because of the presence of other severe accompanying injuries. In most cases, an operation is needed for the prevention of malignant change or infertility. Patient concerns and diagnosis:. We report a case of traumatic testicular dislocation with pelvic fracture and internal bleeding in a 27-year-old male with testis rupture after a motorcycle collision. Interventions and outcomes:. He received emergent right radical orchiectomy, and a series of operations for femoral and pelvic fractures were performed after his condition stabilized in the intensive care unit. After 1 month postsurgery, no obvious genitourinary complications were noted. Conclusion:. We suggest scrotum examination in all trauma patients, particularly if a pelvic injury is suspected or in case of a high risk of a motorcycle collision, to avoid missing the diagnosis and prevent severe complications